Penerapan Metode Technique For Order Preference By Similarity To Idel Solution (TOPSIS) Untuk Penentuan Prioritas Penanganan Pasien Penyakit Stunting Pada Balita - Dwi Normawati; Gentha Muhamad Djamal (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Stunting is a condition that occurs in toddlers who fail to grow due to inadequate nutrition causing the toddler's body size to be abnormal. The stunting examination is carried out by collecting data from the posyandu in each village and then calculating it by the system from the Ministry of Health whose output is data on whether or not stunting is under five. Obstacles in carrying out stunting examinations are in the calculation to determine whether a toddler has symptoms of stunting or not. The system used for calculations is sometimes inaccessible and calculations can only be done by the health center involved. So that the large amount of data available makes the puskesmas overwhelmed and ineffective for inputting data, and the handling of Stunting Disease patients is delayed. This research uses TOPSIS, which is a multi-criteria decision-making method that is commonly used to deal with actual decisions, has a straightforward, efficient concept and can be used as an alternative to measuring performance in the form of simple computational output. TOPSIS uses Euclidean distance to calculate the proximity of an option to the ideal solution, applying the premise that the selected alternative must be geometrically close to the positive ideal solution and furthest from the negative ideal solution. With TOPSIS, the puskesmas can make decisions by determining the weight value for each criterion followed by the ranking stage which produces the selected alternative from a number of alternatives.The alternative with the lowest weighted value is the alternative that has the highest priority. From the TOPSIS method, it is possible to rank decision recommendations where the alternative with the lowest preference value is the chosen alternative to get stunting treatment priority and can later be handled further by an expert in the field.